Empowerment or control?: the history of the Tonga and fishing cooperatives in Binga district 1950-210 - Sinampande, Honour M.M. (Midlands State University, 2017)
The history of the Tonga have it that, the introduction of the fishing villages initially and then later the cooperative system in Binga District from the 1950s-2015 saw the Zambezi Tonga lose their fishing rights. The study traces events paying particular attention to the changes which were introduced to the Tonga fishing practices from the period of the forced relocations to the period 2015. The argument advanced in this research is that the fishing cooperatives system has never benefitted the Tonga people instead other races and ethnicities which were not affected by the induced displacements have. The Tonga fishing rights were taken immediately after the construction of the Kariba Dam. This was followed by the white government also taking control of the lake’s fishing industry both for commercial and sporting reasons. To make matters worse the Tonga who had lived along the Zambezi River were relegated to being mere spectators. This was done by the colonial government’s introduction of fishing communities which were still situated far from where the relocated Tonga had been resettled. The study also looks at the post-colonial government’s policies, notably the cooperative system and the licencing system. These policies were implemented with the aim of empowering the Tonga but in reality they further exploited them. The study also advances the argument of the Tonga not benefitting from the post-colonial government policies by unpacking the effects which were brought by ESAP and the CAMPFIRE programmes to the fishing cooperatives. These two policies came to tighten the already strict policies guarding the Zambezi River leading to continuously clashing of local authorities and the fishermen. In a bid to produce a balanced research a combination of oral, written sources in form of interviews, internet sources, newspapers as well as published and unpolished texts were used